Practical geopolitics in cinematic narratives of Marvel’s The Avengers film franchise - Novak, N. (2021)
This article implies that cinematic narratives project practical geopolitical discourses by using the example of Marvel Cinematic Universe’s success – The Avengers film franchise. The conceptualisation of imaginary threats in the films that follow the main storyline of the Avengers assembly, determined by the time and the geographic space, give those threats a  symbolical manifestation that tends to overlap with the practical geopolitical notions of American foreign policy, as well as contemporary international politics. The interpretative textual analysis of the films’ narratives and their relations to world politics, hence, presents the central methodology of this article. The relation between those two has a capacity to transmit a subconscious message to blockbusters’ consumers about preferable practical geopolitical visions in contemporary world politics. Simply, the paper shows how cinematic narratives form an identity that is deeply securitised and able to capture the Zeitgeist of world’s politics.